1976
DOI: 10.1111/j.1469-8137.1976.tb01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Responses to Vesicular‐arbuscular Mycorrhiza

Abstract: SUMMARY Interactions between vesicular‐arbuscular (VA) mycorrhiza, utilization of rock phosphate and nodulation were examined in three legumes (clover, Stylosanthes and Centrosema) and in onions, grown in eight P‐deficient soils ranging from pH 8.1 to 5.3. Irrespective of pH, inoculation with VA endophytes increased P uptake in all host plants in all the soils when the indigenous endophytes had been removed by irradiation, but appreciable increases in plant dry weight only occurred when P concentrations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
3
4

Year Published

1977
1977
2002
2002

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(61 citation statements)
references
References 20 publications
6
48
3
4
Order By: Relevance
“…(Unfortunately the phosphorus content in nodules was not estimated.) Mosse et al (1976) found that Stylosanthes and Centrosema nodules had twice as iiuieh phosphorus in nodules as in roots and Poschenrieder, Sammet and Fischer (1940) reported tive times more phosphorus in nodules than in roots of soybean.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(Unfortunately the phosphorus content in nodules was not estimated.) Mosse et al (1976) found that Stylosanthes and Centrosema nodules had twice as iiuieh phosphorus in nodules as in roots and Poschenrieder, Sammet and Fischer (1940) reported tive times more phosphorus in nodules than in roots of soybean.…”
Section: Discussionmentioning
confidence: 98%
“…In legumes, VAM not only stimulates plant growth but also nodulation and nitrogen fixation (Crush, 1974;Mosse, Powell and Hayman, 1976;Daft and El-Giahmi, 1976). This appears to be due to better phosphorus nutrition of legumes as a consequence of the mycorrhizal infection.…”
Section: Introductionmentioning
confidence: 99%
“…In groundnut, the increase in the production of shoot biomass may have resulted from maximum utilization of soil available P. Even though only groundnut showed clearly the VAM formation-P nutrition-growth-nitrogen fixation interdependency as reported by many authors for other crops (Mosse et al 1976;Subba Rao et al 1986), the findings reported here may be useful for fertilizer management. This is because information about the period of extensive VAM development and its contribution to P nutrition, growth, N2-fixation, etc., may enable to regulate phosphorus fertilizer applications so as to ensure rapid uptake by crop plants, thereby reducing loss through fixation especially in soils with high P fixation.…”
Section: Resultsmentioning
confidence: 70%
“…In legumes, an increase in the supply of P, whether by fertilisation or mycorrhizae, can increase nodulation, N-fixing activity, and growth (van Schreven 1958;Crush 1974;Gates 1974; Mosse et al 1976; Smith & Daft 1977); increases in weight and P concentration are larger in the nodules than in the rest of the plant (Mosse et al, 1976; de S. Waidyanatha et at. 1979).…”
Section: Introductionmentioning
confidence: 99%